Primary health care: an opportunity for early identification of people living with undiagnosed HIV infection. Issue 6 (24th April 2019) - Martin‐Iguacel, R; Pedersen, C; Llibre, JM; Søndergaard, J; Jensen, J; Omland, LH; Johansen, IS; Obel, N; Rasmussen, LD
Abstract : Objectives: We aimed to determine the fraction of HIV‐diagnosed individuals who had primary health care (PHC) contacts 3 years prior to HIV diagnosis and whether the risk of HIV diagnosis and degree of immunodeficiency were associated with the frequency of visits or procedures performed. Methods: We used data from national registries to conduct a population‐based nested case–control study. Cases were individuals diagnosed with HIV infection in Denmark from 1998 to 2016. Population controls were extracted from the general population matched 13:1 on gender and age. We used conditional logistic regression. As there was a statistically significant interaction, analyses were further stratified by gender and Danish/non‐Danish origin. Results: We identified 2784 cases and 36 192 controls. Ninety‐three per cent of cases and 88% of controls attended PHC at least once in the 3 years prior to diagnosis, with a higher median number of visits to PHC (NVPC) for cases. We found a statistically significant positive association between NVPC and risk of subsequent HIV diagnosis in men and non‐Danish women. A U‐shaped association between NVPC and risk of HIV diagnosis among Danish women. No substantial association between NVPC and degree of immunodeficiency was found. Risk of HIV diagnosis and degree of immunodeficiency were weakly associated with type of procedures performed. Conclusions: For most HIV‐infected individuals, there seem to be many opportunities for earlier diagnosis in PHC. In men and non‐Danish women, the risk of HIV diagnosis but not the degree of immunodeficiency was related to NVPC. The results suggest that the type of medical procedure performed cannot not be used as a guide by the primary physician to indicate which patients to test.